The Importance of Different Elements of English as a Foreign Language for Participation in International Student Mobility Programs: Students’ Perspectives - Miškeljin, Ivana D.; Knežević, Ljiljana J.; Gavrilović, Žana G.; Kurteš, Ognjen M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The aim of this paper is to determine how students from the University of Novi Sad, Serbia, and the University of East Sarajevo, Republic of Srpska, Bosnia and Herzegovina, perceive the importance of certain language skills and aspects of English as foreign language knowledge for participation in international student mobility programs, and whether there are any significant differences between the responses of students from the two universities. To this end, a structured questionnaire was designed and administered among senior-year students from 10 faculties of the University of Novi Sad (N = 727) and 11 faculties of the University of East Sarajevo (N = 264) who participated in mobility programs during the winter semester of the academic year 2024/25. The data were processed using descriptive statistics, a t-test, and the Mann–Whitney U test. The results show that students highly value general communication skills, particularly speaking and listening comprehension, and that students from East Sarajevo—unlike their Novi Sad peers—assign almost equal importance to all areas of knowledge and language skills. The differing perceptions between the students of the two universities reveal several significant differences. Of the 11 survey items, nine show statistically significant differences, including conventions of academic style, everyday communication, extensive vocabulary, specialized vocabulary, grammatical accuracy, excellent pronunciation, oral and written expression on specialized topics, and comprehension of lectures and spoken communication. These findings open avenues for further research and call for similar studies in the Western Balkans to better understand students’ attitudes and create an environment that will encourage more students to take part in mobility programs, given their importance for the internationalization of higher education and greater cooperation among higher education institutions in the region.
Keywords: English as a foreign language; English language skills; international student mobility; internationalization of higher education